Minutes of the 6th Meeting of BRAC University Board of Trustees, BRACU - Board of Trustees (BoT), BRAC University (Vice Chancellor's Office, BRAC University, 2013)
1. Confirmation of the Minutes of the 5th Meeting of the Board of Trustees. 2. Induction of new members in the Board of Trustees. 3. Formation of Board of Trustees under Private University Act 2010. 4. Appointment of Pro-Vice Chancellor. 5. Approval of list of Auditors. 6. Progress of Permanent Campus. 7. Report on Progress of the 8th Convocation. 8. Update on Admission Test. 9. Hiring of Additional Space for BRACU. 10. Issues Regarding JPGSPH. 11. Development of Strategic Plan for IGS. 12. "Future Search" of BRACU. 13. Disciplinary Action. 14. Development of Academic Programs. 15. Review of Syllabi. 16. Academic Results at the end of Spring 2012. 17. Research Centres. 18. Customized EMBA Program. 19. BDI Advisory Group. 20. Guideline for Participating in Print and Electronic Media. 21. Continuation of Study. 22. Presentation on ANSA Project. 23. Appointment of Prof. Dr. Abed Chaudhury as Adjunct Professor. 24. Plagiarism. 25. Rules of Business for Institutes. 26. Rules of Signing Contracts. 27. Professional Skill Development Proaram (PSDP). 28. Appointment of the Academic Staff. 29. Appointment of the Non-Academic Staff. 30. Miscellaneous: 30.1 Appointment of Architect Bashirul Hug as Adjunct Professor. 30.2 Update on Financial Situation of BRACU. 30.3 Review of Scholarship Policy.